A Comparative Performance Evaluation of Islamic and Conventional Funds in South Africa: Array - Abdul Latiff, Arshad (Acta Universitatis Danubius. Œconomica, 2021)
The study comparatively evaluated the performance of Islamic and Conventional funds that comprised of South African unit trusts listed on the Johannesburg Stock Exchange (JSE) vis-à-vis selected market benchmark indices. Whilst the study utilised descriptive statistical analysis for the non-risk adjusted performance analysis, several investment performance models were used for the risk adjusted performance analysis. Relevant statistical tests were performed to decipher relationships between the Islamic fund and the Conventional fund vis-à-vis the selected market benchmarks. Based on the non-risk adjusted performance analysis and absolute risk adjusted performance analysis, the empirical evidence suggests that the Conventional fund performed better than the Islamic fund. However, the relative risk adjusted performance analysis shows a mixed overall result during the entire period of the study. While the Modigliani & Modigliani measure and Jensen alpha showed that the Conventional fund performed better than the Islamic fund from a risk adjusted return perspective, the Treynor ratio showed that the Islamic fund performed better than the Conventional fund. More so, while the t-test analysis suggests that there is no statistically significant evidence to support that the Islamic fund under or outperforms the Conventional fund, the correlation analysis showed that both funds are more positively correlated and statistically significant with the South African market indices. The findings of the study imply that an investment in the Conventional fund would have offered a superlative non-risk adjusted return than the Islamic fund. Also, the relative risk adjusted performance imply that upon the diversification of unsystematic risks in some market indices, the Islamic fund may perform better than the Conventional fund.